Critical observations about the sentinel lymph node in colorectal cancer - Zenén Rodríguez Fernández (Universidad de Ciencias Médicas de La Habana, 2018)
Introduction: The identification of the sentinel lymph node during surgical treatment of colorectal cancer can help the correct postoperative staging and go beyond adjuvant chemotherapy in the follow-up of patients with the aim to improve survival of these sick people. Objective:  To identify the techniques used to detect the sentinel lymph node through either conventional or laparoscopic approach: staining or radiotracer "ex vivo" or "in vivo", as well as its influence in postoperative staging and the adjuvant treatment correlated with the evolution of colon cancer.  Material and Methods: Document review of up-to-date publications about the topic in both electronic and printed formats. Development:The study of lymphatics is considered the most important prognostic factor in the colorectal cancer without metastases.  The detection of the sentinel node is the technique that best predicts the lymph node status in a patient, and allows to conduct intensive studies to improve staging. Conclusions:The study of the sentinel lymph node is a reproducible practice without a significant increase in time and costs. The follow-up of patients classified as NO with a positive sentinel lymph node seems to have a tendency to a higher percentage of relapses, which could go beyond changes in the adjuvant treatment guidelines aimed at improving survival. Keywords:sentinel lymph node, colorectal cancer, staging, surgery, adjuvant treatment